2018
DOI: 10.12775/hip.2018.023
|View full text |Cite
|
Sign up to set email alerts
|

Współczesne determinanty bezpieczeństwa powietrznego państwa

Abstract: H i s t o r i a i P o l i t y k a Nr 25(32)/2018, s s. 65 -80 w w w.h ip.u m k .pl ISSN 1899 -516 0, e-ISSN 2391-7652• A b s t r a k t • W artykule przedstawiono wyniki badań, które koncentrują się na współczesnych aspektach związanych z bezpieczeństwem powietrznym państwa w okresie pokoju i wojny. W pierwszej części rozważania naukowe miały na celu identyfikację aparatury pojęciowej związanej z koncepcją bezpieczeństwa powietrznego państwa, zagrożenia powietrznego i obrony powietrznej. W dalszej części autor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A key role in countering air terrorism is played by operations with the use of special forces detached from the armed forces of particular countries. Other important documents that define the rules of using military force in combating acts of terror are as follows: the concept of operational reinforcement of the NAtO air-defence system against a possible terrorist attack, using civil aircraft (MCM-062-2) and the revised NAtO Directive on the functioning of an integrated force OP NAtO- (Radomyski 2018). No-fly zones or flight restricted zones are preceded by identification zones, in which a final verification of an aircraft as confirmed target or accidental intruders is provided.…”
Section: Diagnosis Of Ways Methods and Measures Used To Counter Air mentioning
confidence: 99%
“…A key role in countering air terrorism is played by operations with the use of special forces detached from the armed forces of particular countries. Other important documents that define the rules of using military force in combating acts of terror are as follows: the concept of operational reinforcement of the NAtO air-defence system against a possible terrorist attack, using civil aircraft (MCM-062-2) and the revised NAtO Directive on the functioning of an integrated force OP NAtO- (Radomyski 2018). No-fly zones or flight restricted zones are preceded by identification zones, in which a final verification of an aircraft as confirmed target or accidental intruders is provided.…”
Section: Diagnosis Of Ways Methods and Measures Used To Counter Air mentioning
confidence: 99%
“…Currently, we are witnessing a cycle of modernizing fourth-generation fighters in many countries to keep them in service for several more decades until they are eventually replaced by fifth and subsequent generation fighters. These modernizations primarily focus on enhancing the survivability of the aircraft, primarily through the installation of electronic self-defense systems that disrupt and deceive the enemy's sensors and effectors (Radomyski, 2014). A significant aspect of upgrading older aircraft involves replacing the existing radars with new ones featuring active electronically scanned array (AESA) technology, which can operate in active, passive, and electronic warfare modes.…”
Section: Future Manned Air Threatsmentioning
confidence: 99%
“…When dealing with threats arising from human activity, the threats will be related to a possibility of launching an attack by an aircraft on military installations or civil objects which are relevant to the functioning of a state (Leksykon wiedzy o obronności Polska i Europa [Lexicon of Knowledge on Poland and Europe's Defense], 2014). A more complete definition of air threats is presented by Adam Radomyski, who claims that an air threat must be regarded as a state which disturbs the feeling of security in a state (in all its dimensions), resulting from a threat of the use of aircraft (platforms) by a potential state or non-state aggressor (Radomyski, 2018). It can, therefore, be concluded that an air threat is a dangerous situation, in which there is every likelihood of using an aircraft/apparatus/weapons (civil or military) by a state or non-state actor, or its part.…”
Section: Determinants Of Air Threatsmentioning
confidence: 99%